(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study analyzes the level of transparency of financial information disclosed on the institutional portals of Research Support Foundations (FAPs) in Northeast Brazil. Using a quantitative and qualitative approach, it uses the criteria of Almada et al. as a reference, complemented by usability, accessibility, and legal compliance indicators. The comparative analysis between Fapeal and Funcap highlights inequalities in data organization and availability. The results indicate weaknesses in active transparency and point to ways to strengthen digital governance and informational citizenship.